Hypoxia in Tumor Microenvironment and Chemotherapy Resistance: Understanding the Impact of Hypoxia on Chemotherapy Resistance (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Hypoxic region in tumors is characterized by an aberrant vascular network concomitant with cellular re-programming. This survival strategy in an aggressive tumor microenvironment, ultimately promotes tumor growth. Hypoxia-activated transcriptional factors such as HIF, NF-kB etc. govern tumor growth and progression. A large number of therapeutic methods have targeted this tumor’s growth. However, development of resistance to treatments is one of the major problems. Hypoxia a component of tumor microenvironment plays crucial role in development of resistance to therapeutic approaches. In this review, we have summarized the most relevant findings to address the involvement of hypoxia in resistance to a variety of drugs. It is also discussed that hypoxia induced biological variations in tumor cells, which further facilitates chemo resistance. This will aid in grasping the key role played by hypoxia in chemo resistance and will be helpful in development of improved chemotherapeutic methods.